2000
DOI: 10.1046/j.1365-2621.2000.00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of internal atmosphere and humidity in perforated packages of peeled garlic cloves

Abstract: Summary A mathematical model was developed for estimating the changes in the atmosphere and humidity within perforated packages of fresh produce. The model was based on the mass balances of O2, CO2, N2 and H2O vapours in the package, which include terms for their transfer through perforations and film, respiration and water transpiration. The model was verified by comparing predicted and measured gas compositions and relative humidities inside experimental packages of peeled garlic cloves stored at 5 and 20 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Several researchers have reported that humidity inside most fresh produce packages is saturated, which results in moisture condensation on the package surface. 1,5,24,25 As shown in Table 2, the gas permeability of unglazed earthenware was significantly reduced with saturated humidity conditions, whereas there was only a very slight difference due to moisture saturation for the glazed earthenware. With moisture condensation of the unglazed earthenware surface and a slight temperature build-up inside the package, the microporous structure may have been changed, so that the gas permeability was decreased.…”
Section: Figure 1 Scanning Electron Micrographs Of the Internal And mentioning
confidence: 93%
“…Several researchers have reported that humidity inside most fresh produce packages is saturated, which results in moisture condensation on the package surface. 1,5,24,25 As shown in Table 2, the gas permeability of unglazed earthenware was significantly reduced with saturated humidity conditions, whereas there was only a very slight difference due to moisture saturation for the glazed earthenware. With moisture condensation of the unglazed earthenware surface and a slight temperature build-up inside the package, the microporous structure may have been changed, so that the gas permeability was decreased.…”
Section: Figure 1 Scanning Electron Micrographs Of the Internal And mentioning
confidence: 93%
“…MAP has been successfully applied to preserve several vegetables including broccoli, cauliflower, carrots, garlic and others [20]. The effect of the packaging has been studied on the quality of broccoli [21] and cauliflowers [22].…”
Section: Map Uses To Preserve Vegetables and Fruitsmentioning
confidence: 99%
“…Lee et al (2000) investigated the dynamics of internal atmosphere and humidity in perforated plastic packages of peeled garlic. These workers developed a mathematical model which can predict the changes that take place in the package atmosphere over time: however, they found that hermetic packaging, which produced a water-saturated atmosphere with nil O 2 and 5% to 15% CO 2 , performed better than perforated plastic in maintaining the freshness of the peeled cloves.…”
Section: Research On Prepared Allium Productsmentioning
confidence: 99%